Implementing Blended Learning in Vocational High Schools: A Comprehensive Workshop - Arifin, Rusjdy Sjakyakirti; Darmansyah, Dina Febriani; Ramadi, Rikaro; Alfariji, Muhammad Dandi; Dhaifullah, Ahmad Maulana; Wijaya, Muhammad Fa’iq (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
The COVID-19 pandemic highlighted the critical need for technological integration in education, showcasing the potential of e-learning to significantly enhance both instructional efficacy and efficiency. To capitalize on these advancements post-pandemic, this study concentrates on the implementation of Blended Learning—a pedagogical method that merges traditional face-to-face instruction with online learning—in vocational senior high schools. Despite its numerous advantages, the adoption of Blended Learning remains limited in many schools due to various challenges. This community service initiative is designed to equip vocational school instructors and educational personnel with the skills required to seamlessly integrate Blended Learning into their teaching methodologies. The program includes a series of workshops and technical training sessions, systematically divided into three phases: assessment, implementation, and evaluation. Scheduled for August 2023, the workshop is aimed at educators and educational professionals, offering them hands-on experience and practical knowledge essential for this hybrid instructional approach. Initial results suggest that participants achieved a thorough understanding of Blended Learning's benefits and displayed a strong readiness to adopt this instructional strategy, as demonstrated by pre- and post-workshop assessments and feedback surveys. feedback surveys.